Analysis of the propellers-airframe interaction of the light transport aircraft - Yu. S. Mikhailov (Научный вестник МГТУ ГА)
In the design of multi-engine aircraft, one of the important issues is the interaction between the propellers and airframe configuration components, especially in take-off and go-around procedure modes. Modern propeller-driven aircraft concepts in the pulling configuration are characterized by a high disk loading and an increased number of propeller blades used to increase cruising speed and reduce excessive noise. The first problem arising due to high disk loading is the direct impact of forces by operating propellers (thrust, normal force) on fixed-wing stability, especially at angles of attack different from a zero value. The second one involves a high-energy level of the propeller slipstream, having a significant indirect impact on the aircraft’s aerodynamics, stability and controllability. This impact is primarily associated with the interaction of propellers slipstream with other aircraft’s configuration elements. The complexity of taking into account the slipstream-wing interaction and other airframe components stipulated the application of experimental methods to study the problems of propellers – airframe interaction while designing propeller-driven aircraft configurations. This article presents an analysis of the experimental studies results of the operating propellers- airframe interaction for a light twin-engine transport aircraft. The aerodynamic aircraft’s configuration is executed using the conventional pattern of a high-wing and the carrier-on deck type empennage. The high-lift wing device is a fixed-vane doubleslotted flap. The wind-tunnel tests of the model in the cruising, takeoff and landing configurations were carried out in TsAGI lowspeed wind-tunnel T-102. Measurement of forces and moments, acting on the model, was performed by means of an external sixcomponent wind-tunnel balance. Measurement of forces and moments, acting on the propeller, was conducted using strain gauge weighers installed inside the engine nacelles of power plant simulators. The simultaneous combined use of external and internal balances allowed researchers to determine the direct and indirect contribution of operating propellers to the model longitudinal aerodynamic characteristics under variation of loading factor B ranging from 0 to 2.